Supercapacitor Design and Applications - Stevic, Zoran (IntechOpen, 2016)
In this book, authors investigated asymmetric and symmetric supercapacitor configurations for different electrode materials. Besides the already standard activated carbon (AC), studies were done with other materials and technologies for their preparation and activation. Also, the research info was presented with different electrolytes in order to obtain a higher capacitance and potential window, with as small as possible serial resistance. Achieved high performance enables wide application, and some of the new applications (spacecraft power systems, powering heart pacemakers and wireless sensors) are also described in this book.